2019
DOI: 10.1016/j.energy.2019.03.165
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a combination of three heat sources for heat pumps to supply district heating

Abstract: This paper reports a study on how hourly temperature variations of different heat sources influence the seasonal coefficient of performance (SCOP) of heat pumps (HPs) when supplying district heating. The considered heat sources were: groundwater, seawater, air and a combination of the three. The system included HPs, an electric peak load boiler and short-term storage. Linear programming was used to minimize annual electricity consumption of the system. This process also determined the optimum capacities of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…It must be highlighted that this scale effect is even more noticeable in real district heating systems, as the combination of different energy sources allows the efficiency to be enhanced through the modulation and supply chain of the different used fuels. This effect was not shown in this study, as it focused on theoretical cases across Europe (single energy source with a natural gas complement), but it was demonstrated in [75] for heat pumps and in [76] for solar-assisted groundwater sourced heat pumps.…”
Section: Conclusion and Discussionmentioning
confidence: 73%
“…It must be highlighted that this scale effect is even more noticeable in real district heating systems, as the combination of different energy sources allows the efficiency to be enhanced through the modulation and supply chain of the different used fuels. This effect was not shown in this study, as it focused on theoretical cases across Europe (single energy source with a natural gas complement), but it was demonstrated in [75] for heat pumps and in [76] for solar-assisted groundwater sourced heat pumps.…”
Section: Conclusion and Discussionmentioning
confidence: 73%
“…However, when domestic electricity demand is reduced, the shift to district heating might increase the risk of export to drain reservoirs. Pieper et al [133] reported the influence on the seasonal coefficient of performance (SCOP) of a DHC system when introducing seawater, groundwater, air and a combination of the three as energy sources. The results showed that the optimum proportions of DHC capacity with groundwater, seawater and air heat pumps were 63%, 14% and 23%, respectively.…”
Section: Development Of District Heating Systemmentioning
confidence: 99%
“…Here, I assume that all the residential heating systems will be replaced by heat pumps with an average coefficient of performance (COP) of 2.0. Higher COP's are possible by using a heat source with a higher temperature, that can be used to update these estimations; see, e.g., [32][33][34].…”
Section: Low-temperature Heatmentioning
confidence: 99%